Awareness of genetic risk in the Dominantly Inherited Alzheimer Network (DIAN). Issue 1 (8th January 2020) - Aschenbrenner, Andrew J.; James, Bryan D.; McDade, Eric; Wang, Guoqiao; Lim, Yen Ying; Benzinger, Tammie L.S.; Cruchaga, Carlos; Goate, Alison; Xiong, Chengjie; Perrin, Richard; Buckles, Virginia; Allegri, Ricardo; et al.
Abstract: Introduction: Although some members of families with autosomal dominant Alzheimer's disease mutations learn their mutation status, most do not. How knowledge of mutation status affects clinical disease progression is unknown. This study quantifies the influence of mutation awareness on clinical symptoms, cognition, and biomarkers. Methods: Mutation carriers and non‐carriers from the Dominantly Inherited Alzheimer Network (DIAN) were stratified based on knowledge of mutation status. Rates of change on standard clinical, cognitive, and neuroimaging outcomes were examined. Results: Mutation knowledge had no associations with cognitive decline, clinical progression, amyloid deposition, hippocampal volume, or depression in either carriers or non‐carriers. Carriers who learned their status mid‐study had slightly higher levels of depression and lower cognitive scores. Discussion: Knowledge of mutation status does not affect rates of change on any measured outcome. Learning of status mid‐study may confer short‐term changes in cognitive functioning, or changes in cognition may influence the determination of mutation status.